METHODOLOGICAL MEANS OF DEVELOPING A CULTURE OF TOLERANCE IN HIGH SCHOOL STUDENTS IN THE EDUCATIONAL PROCESS - Yusupova Maftuna Ilxomiddin qizi (International Journal of Literature and Language Studies, 2026)
Abstract The formation of a culture of tolerance among high school students has become one of the most important objectives of modern education. Globalization, migration processes, intercultural communication, and the increasing diversity of societies require educational institutions to prepare young people for constructive interaction in multicultural environments. This article examines the methodological means of developing a culture of tolerance among high school students within the educational process. The study analyzes theoretical foundations, pedagogical approaches, interactive teaching methods, value-based education, project-based learning, cooperative learning technologies, extracurricular activities, and digital educational resources that contribute to the formation of tolerant attitudes and behaviors. The research highlights the role of teachers, school environments, and educational policies in promoting tolerance. Recommendations are provided for improving educational practices aimed at strengthening tolerance culture in secondary schools.